Introduction to the Univariate Analysis of Trends in Economic Time Series - Artur Silva Lopes (ZBW – Leibniz Information Centre for Economics, 2025)
This book provides a comprehensive and systematic review of most of the literature on the univariate analysis of trends in economic time series. It also provides original insights and criticisms on some of the topics that are addressed. Its chapter structure is as follows. 1 Introduction (preliminary issues). 2 Historical perspective. 3 Modeling the trend. 4 Decomposition methods. 5 Testing for the presence of a trend. Annex: A brief introduction to filters.
Keywords: B23; C22; C51; C52; E32; O47; 330; trend; long-run; low-frequency; linear trend; nonlinear trend; decomposition of time series; filtering; detrending; business cycles